Pengaruh kualitas produk, pengetahuan produk, variasi produk, bagi hasil dan syariah compliance terhadap loyalitas nasabah: Studi kasus BMT UGT Nusantara Malang - Hasanah, Devi Homsatun (Maliki Interdisciplinary Journal, 2023)
This study aims to determine the effect of product quality, product knowledge, product variety, profit sharing and sharia compliance on customer loyalty of BMT UGT Nusantara Malang. This research was conducted using an associative quantitative approach with the number of samples used in this study amounting to 300 respondents who came from customers of BMT UGT Nusantara Malang. The analysis used in this study is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing (partial test and simultaneous test). The results of this study indicate that the variables of product quality, product knowledge, product variety, profit sharing and Sharia Compliance simultaneously or simultaneously influence the customer loyalty variable. Based on the partial test, it shows that the only variables are product quality and product knowledge that affect customer loyalty, while other variables do not have a partial effect on customer loyalty.